Insights into immuno-oncology drug development landscape with focus on bone metastasis - Kähkönen, Tiina E.; Halleen, Jussi M.; MacRitchie, Gary; Andersson, Ronnie M.; Bernoulli, Jenni (Frontiers in Immunology, 2023)
Bone is among the main sites of metastasis in breast, prostate and other major cancers. Bone metastases remain incurable causing high mortality, severe skeletal-related effects and decreased quality of life. Despite the success of immunotherapies in oncology, no immunotherapies are approved for bone metastasis and no clear benefit has been observed with approved immunotherapies in treatment of bone metastatic disease. Therefore, it is crucial to consider unique features of tumor microenvironment in bone metastasis when developing novel therapies. The vicious cycle of bone metastasis, referring to crosstalk between tumor and bone cells that enables the tumor cells to grow in the bone microenvironment, is a well-established concept. Very recently, a novel osteoimmuno-oncology (OIO) concept was introduced to the scientific community. OIO emphasizes the significance of interactions between tumor, immune and bone cells in promoting tumor growth in bone metastasis, and it can be used to reveal the most promising targets for bone metastasis. In order to provide an insight into the current immuno-oncology drug development landscape, we used 1stOncology database, a cancer drug development resource to identify novel immunotherapies in preclinical or clinical development for breast and prostate cancer bone metastasis. Based on the database search, 24 immunotherapies were identified in preclinical or clinical development that included evaluation of effects on bone metastasis. This review provides an insight to novel immuno-oncology drug development in the context of bone metastasis. Bone metastases can be approached using different modalities, and tumor microenvironment in bone provides many potential targets for bone metastasis. Noting current increasing interest in the field of OIO, more therapeutic opportunities that primarily target bone metastasis are expected in the future.